The management in the sphere of physical culture and sport at the level of administrative and territorial units: traditions and innovations - Савченко, Віктор Григорович; Сергеєв, Андрій Юрійович (Slobozhanskyi Herald of Science and Sport, 2016)
Savchenko V., Sergeiev A. Purpose: to analyze the activity of subjects of management in the sphere of physical culture and sport at the level of territorial administrative units. Material & Methods: the legal analysis of a feature of management in the sphere of physical culture and sport of administrative and territorial units of the various level. Results: the main activities of administrative structures of the governmental authorities and the local governments are allocated. Conclusions: it is revealed that the sphere of physical culture and sport needs the improvement in the conditions of decentralization, offers on its reforming are considered.